2011
DOI: 10.1371/journal.pone.0028285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Acanthocephala (Class Palaeacanthocephala) with a Paraphyletic Assemblage of the Orders Polymorphida and Echinorhynchida

Abstract: Acanthocephalans are attractive candidates as model organisms for studying the ecology and co-evolutionary history of parasitic life cycles in the marine ecosystem. Adding to earlier molecular analyses of this taxon, a total of 36 acanthocephalans belonging to the classes Archiacanthocephala (3 species), Eoacanthocephala (3 species), Palaeacanthocephala (29 species), Polyacanthocephala (1 species) and Rotifera as outgroup (3 species) were analyzed by using Bayesian Inference and Maximum Likelihood analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
70
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 29 publications
15
70
0
1
Order By: Relevance
“…It is noteworthy that the present mitochondrial phylogeny demonstrated Palaeacanthocephala to be monophyletic and to be closely related with Eoacanthocephala. Palaeacanthocephalan monophyly has been widely supported by most of previous analyses of morphological [18] and molecular data (SSU rDNA [7,8,19,20,23,24], SSU rDNA + mtDNA cox1 [9]). However, phylogenetic analysis of SSU rDNA data with different taxon sampling and alignment reported its non-monophyly [25]: the Echinorynchus group was basal to (Eoacanthocephala (Leptorhynchoides group + Archiacanthocephala)).…”
Section: Phylogenetic Relationships Among Major Acanthocephalan Groupsmentioning
confidence: 81%
See 1 more Smart Citation
“…It is noteworthy that the present mitochondrial phylogeny demonstrated Palaeacanthocephala to be monophyletic and to be closely related with Eoacanthocephala. Palaeacanthocephalan monophyly has been widely supported by most of previous analyses of morphological [18] and molecular data (SSU rDNA [7,8,19,20,23,24], SSU rDNA + mtDNA cox1 [9]). However, phylogenetic analysis of SSU rDNA data with different taxon sampling and alignment reported its non-monophyly [25]: the Echinorynchus group was basal to (Eoacanthocephala (Leptorhynchoides group + Archiacanthocephala)).…”
Section: Phylogenetic Relationships Among Major Acanthocephalan Groupsmentioning
confidence: 81%
“…Despite good resolution of acanthocephalan internal phylogeny either from morphology and/or from molecular data, palaeacanthocephalan monophyly has not always been supported. Several analyses based on morphology [18] and molecular data [7][8][9]19,20,23,24] depicted Palaeacanthocephala as monophyletic, but phylogenetic analysis of SSU rDNA data with different taxon sampling and multiple alignment yielded non-monophyly [25]. Very recent analysis for mitochondrial genome sequences resulted in a monophyletic group for two palaeacanthocephalan representatives (Echinorhynchus truttae [nad4 and nad4L genes were missing], Leptorhynchoides thecatus) [22], both belonging to the order Echinorhynchida of Palaeacanthocephala.…”
Section: Introductionmentioning
confidence: 99%
“…has been already recorded for E. coioides at both sampling sites with a similar prevalence of infection (2.9 -8.6% in Segara Anakan region versus 20.0 -28.6% in Bali) (Kleinertz, 2010). The recorded Serrasentis sagittifer (Acanthocephalan) had already been found in the Segara Anakan region by Theisen (2009) in three different fish species (J. coitor, N. japonicus and Platycephalus arenarius; see also Verweyen et al, 2011). Rü ckert (2006 and Rü ckert et al (2009bRü ckert et al ( , 2010 suggested the epinephelids E. coioides and E. fuscoguttatus as paratenic and/or transport hosts for these species.…”
Section: Sa 4 2009 B 2009mentioning
confidence: 89%
“…The 660 bp long fragment of COI was amplified using primers LCO 1490 and HCO 2198 (Folmer et al 1994), the approx. 1,700 bp long 18S rRNA gene was amplified using the forward primer 18S ACF (5´-AGATTAAGCCATGCATGCGTAAG-3´) and the reverse primer 18S ACR (5´-TGATCCTTCTGCAGGTTCACCTAC-3´) (Verweyen et al 2011), the approx. 1,500 bp long ITS was am-plified using the forward primer ac58f (5´-GTCGTAACAAGGT-TTCCGT-3´) and the reverse primer ac1500r1 (5´-CGATTGAT-TTGCACGTC-3´) (Tkach et al 2013), and the approx.…”
Section: Procedures For Molecular Studymentioning
confidence: 99%